Impact of a collective mentorship programmers on reducing depression and improving the self-esteem of Syrian female students in the Za 'atari camp - Keelani, Na'ela Odeh Abedalqader (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to learn about the impact of a collective mentorship programmers in reducing depression and improving the self-esteem of female Syrian students in the Za 'atari camp. The study included a sample of the basic study consisting of (30) pupils, distributed to the experimental group (15) and control group (15), adopting the experimental curriculum according to tribal and postgraduate measurements, were selected in the purpose manner of the total number of female students attending school in grades 7 and 8 in the 2022/ 2023 year in the camp of Za’tari Jordan. The study's findings were as follows: Results showed: statistically significant differences at the indicative level (α= 0.05) between the average scores of the experimental group and the control group in the dimensional measurement on the depression scale and the self-assessment scale in favor of the experimental group, indicating the effectiveness and efficiency of the indicative program in reducing depression and improving self-esteem. It also showed that there were no statistically significant differences at the indicative level (α= 0.05) between the experimental sample members' score averages on depression and self-esteem measurements, indicating that the program's effectiveness in the pilot study sample was consistent in the follow-up measurement. The study recommended several recommendations: further studies using similar indicative programmes among different variables and other disorders because of the study's positive results in reducing depression. Training of instructors and educators in the preparation of the indicative program to improve students' self-esteem. To call on the Ministry of Education to adopt the indicative programmers to prove its effectiveness in reducing depression and making adjustment among school members. The need to work to detect the manifestations and causes of depression at the beginning of their emergence, and to work for early intervention to reduce them so that these disorders do not develop into more serious behaviors in the future.
Keywords: collective guidance; depression; self-esteem; Syrian female students; Za'atari camp